Edukasi Kesehatan Mengenai Deteksi Dini Penyakit Demam Dengue dan Demam Tifoid di SMP Negeri 11 Kota Samarinda - Dantie Gustia Atiqa Putri; Muhammad Taufik Hidayat; Akhmad Jaizzur Rijai (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
The similarity of early symptoms between Dengue Fever and Typhoid Fever in adolescents often leads to dangerous delays in medical treatment. This health promotion activity aimed to improve the knowledge of grade VII A students at SMPN 11 Samarinda regarding early detection and preventive measures for both diseases. The educational method involved interactive lectures using PowerPoint presentation and leaflet distribution to 29 participants. The level of understanding was evaluated by comparing pre-test and post-test scores. The results showed a highly positive response, demonstrated by a significant increase in the students' average knowledge score from 83.8% in the pre-test to 89.3% in the post-test. In conclusion, this health education intervention is effective in equipping students to recognize specific symptoms, warning signs, and early preventive actions against infectious diseases within the school environment